THE SOUTH OF RUSSIA IN THE FIELD OF MIGRATION PROCESSES -MODERN CHALLENGES AND THREATS BLACK SEA-CASPIAN REGION - Rafik Hammatovich Usmanov (Современная наука и инновации, 2022)
The article is devoted to modern ethno-political processes in the South of Russia. Based on recent studies of modern ethno- political processes shows the new threats and challenges of uncontrolled migration flows from the Middle East and North Africa. Such processes have created a serious threat not only to EU countries but also in other continents. The author of the analysis andforecast of the growing conflict potential in the Black Sea-Caspian region, which concerns in particular the South of Russia. On the basis of a comparative analysis of the old and the modern conlict concludes succession of negative processes data due to lack of development of democratic processes and the low level of tolerance in the regions of the North Caucasus, which is fertile ground for the development of Islamic radicalism.